Studying the Frequency of Favorable Allele of rs12979860 Polymorphism of IL-28B in Healthy and HCV Infected Iranian Individuals - Abdolvahab Alborzi; Tayebeh Hashempour; Mahboobe Mirhoseini; nasim Adim; Javad Moayedi; Zahra Musavi; Shahin Merat; Gholam Reza Pouladfar; Mehrdad Hallaji; Farzaneh Ghassabi; Arghavan Haj-Sheykholeslami (Fasa University of Medical Sciences, 2015)
Background & Objective: Hepatitis C Virus (HCV) is one of the important risk factors for liver cirrhosis and hepatocellular carcinoma. Some of the host genetic factors such as interleukin 28B (IL-28B) may influence the response to the antiviral therapy. IL28B is a member of the interferon (IFN) family which causes an antiviral response. Previous studies indicated that rs12979860 polymorphisms of the IL-28B gene can influence persistent antiviral response. Therefore, in this study, the frequency of genotypes of rs12979860 polymorphisms in two groups of healthy and HCV infected Iranian individuals were evaluated. Materials & Methods: In this cross sectional study, PCR-RFLP method was used to evaluate the frequency of genotypes of rs12979860 polymorphisms in 105 healthy individuals and 105 chronic HCV infected patients. Results: The frequency of rs12979860 genotypes in healthy individuals was CC: 50.5%, CT: 45.7%, and TT: 3.8%. In HCV infected patients it was CC: 22.9%, CT: 63.8%, and TT: 13.3%. The frequency of rs12979860 genotypes had significant difference between two groups however it is not associated with sex. Conclusion: A significant difference was observed between healthy individuals and HCV infected patients in the frequency of rs12979860 genotypes. The favorable CC genotypes and unfavorable TT genotypes was more detected in healthy individuals and HCV infected patients, respectively.